Language at large : essays on syntax and semantics - Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna) (Empirical approaches to linguistic theory ;, 2011)
The volume brings together important essays on syntax and semantics by Aikhenvald and Dixon. It focusses on topics in linguistic typology, the analysis of previously undescribed languages and issues in the grammar and lexicography of English.